Redesigning User Interface Using Prototype Method on The Scholarship Acceptance System - Anisa Hudi Widaningrum; Rissa Dwi Kurnia Tanti; Nakhla Ahmad Dreykha; Fernantyo Krisnajati; Novia Ratnasari (Universitas Islam Raden Rahmat, Malang, 2025)
This study aims to redesign the user interface (UI) of the KIP-K scholarship recipient prediction system at the Garut Institute of Technology by adding academic and non-academic monitoring features. The main issue raised is the lack of a system that can comprehensively monitor the progress of scholarship recipients. The research method used is qualitative descriptive, utilizing secondary data and six stages of system development, from literature review to testing. The design process was conducted using low-fidelity and high-fidelity prototyping approaches to produce a more functional and user-friendly interface design. System testing was conducted using usability testing through the Maze.co platform and heuristic evaluation based on Nielsen's 10 principles. The test results showed that most users were satisfied with the developed system, although some heuristic principles were not yet met. These results serve as the basis for further improvements to enhance the effectiveness and efficiency of managing and monitoring KIP-K scholarships.